Antisolvent‐Induced Fastly Grown All‐Inorganic Perovskite CsPbCl3 Microcrystal Films for High‐Sensitive UV Photodetectors. Issue 6 (8th February 2021) - Zhu, Zhihao; Deng, Wen; Li, Wen; Chun, Fengjun; Luo, Chao; Xie, Meilin; Pu, Ben; Lin, Na; Gao, Bo; Yang, Weiqing
Abstract: CsPbCl3 ‐based inorganic perovskite ultraviolet photodetectors (UV‐PDs) have a great promise for the wide application prospects due to the desirably UV‐matched energy band and the excellent intrinsic optoelectronic properties. However, the traditional high‐temperature Bridgman method (near 600 °C) and complexly time‐consuming vapor preparation (several days) of high‐quality CsPbCl3 crystals have badly restricted its commercial applications to date. Herein, an antisolvent‐induced crystallization kinetics (ACK) strategy is demonstrated for the quick lower‐temperature fabrication (50 °C, tens of minutes) of excellent continuous highly crystalline CsPbCl3 microcrystal films (MCFs) with low trap density (1.42 × 10 12 cm −3 ). Further, the as‐developed CsPbCl3 MCF‐based UV‐PDs present a high detectivity of 5.6 × 10 12 Jones, a superior responsivity of 2.11 A W −1, and robust stability. Evidently, this work provides a rapid and simple method to prepare high‐quality perovskite MCFs, greatly promoting the commercial development of perovskite‐based photodetectors. Abstract : The high‐quality CsPbCl3 microcrystal films with extremely low defect state density are prepared by antisolvent‐induced crystallization kinetics strategy. Due to the wide bandgap of CsPbCl3, it is suitable for ultraviolet photodetection. A suitable device structure is designed, and the prepared ultraviolet photodetector based on CsPbCl3 microcrystalline film has good detection performance for ultraviolet light.